A Nonmetallic Stretchable Nylon‐Modified High Performance Triboelectric Nanogenerator for Energy Harvesting. (11th November 2019) - Qian, Jichao; He, Jian; Qian, Shuo; Zhang, Jing; Niu, Xushi; Fan, Xueming; Wang, Chao; Hou, Xiaojuan; Mu, Jiliang; Geng, Wenping; Chou, Xiujian
Abstract: As a new energy harvesting strategy, triboelectric nanogenerators which have a broad application prospect in collecting environmental energy, human body mechanical energy, and supplying power for low‐power electronic devices, have attracted extensive attention. However, technology challenges still exist in the stretchability for the preparation of some high‐performance triboelectric materials. In this work, a new strategy for nonmetallic nylon‐modified triboelectric nanogenerators (NM‐TENGs) is reported. Nylon is introduced as a high performance friction material to enhance the output performance of the stretchable TENG. The uniform matrix reduces the difficulty of heterogeneous integration and enhances the structural strength. The open‐circuit voltage ( V OC ) and short‐circuit current ( I SC ) of NM‐TENG can reach up to 1.17 kV and 138 µA, respectively. The instantaneous power density reaches 11.2 W m −2 and the rectified output can directly light ≈480 LEDs. The transferred charge density is ≈100 µC m −2 in one cycle when charging the capacitor. In addition, a low‐power electronic clock can be driven directly by the rectified signal without additional circuits. NM‐TENG also has high enough strain rate and can be attached to the human body for energy harvesting effectively. This work provides a new idea for fabrication of stretchable TENGs and demonstrates their potential application. Abstract : A strategy for the modification of stretchable triboelectric nanogenerators (TENGs) using nonmetallic polymers is proposed. The nylon‐modified‐TENG provides a very high output performance ( V OC = 1.17 kV, I SC = 46 mA m −2, W = 11.2 W m −2 ) and a satisfactory strain property. This device can be used for energy harvesting for mechanical structure, human motion, etc.